Older People and Well-Being: Perception and Influencing Factors - Spillane, Mairead (STER, 2019)
The dearth of research into the subjective experiences of older people living in the community setting was a key motivation for this study. The aim of which was to explore the older person’s subjective perception of the factors which impact their well-being rather than the previously much studied professional perspectives. This study seeks to create a better understanding of the process of ageing and to reflect the experiences, beliefs and abilities of older people themselves. This research explores the facilitators and barriers to the layperson’s positive perception of wellbeing provides an important contribution to the body of knowledge. Understanding the older person’s perception of well-being is necessary to inform strategic planning and future public policy.
Journal article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Well-being; Health; Aging; Education